The modern approach to treatment of malignant bone tumours (Part 1) (Review of literature) - Vyrva, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The first part of this review of medical literature about the modern state of the problem of treatment of bone tumours shows that these neoplasms belong to the least studied group with significant positive changes in their treatment during past years. Early detection of pathological foci prevents malignant transformation of benign tumours and tumour-like diseases. Use of up-to-date techniques of examination and modern protocols of multimodality therapy for malignant tumours provides positive long-term results. Individual multimodality therapy of malignant tumours of bones includes neoadjuvant and adjuvant polychemotherapy (PCT), radiation therapy, immunotherapy, plastic surgery, vascular interventions and other methods with compulsory pathomorphological verification of the disease and continuous monitoring for correction of the proper therapy. The concrete clinical situation having been assessed, the method of treatment is agreed by the oncoorthopaedist, oncologist, radiologist, chemotherapeutist and rehabilitation therapist, whose cooperation contributes to creation of the optimum plan of treatment. The chief aim of management of the patient with a malignant bone tumour must consist in effective organ-salvation treatment, the latter being given with observation of principles of ablastics. It is shown that organ-salvation operations are regarded today as the best method of treatment for thoroughly selected patients with osteosarcomata. Amputation is made when it is impossible to remove the primary tumour because of technical problems or a severe, life-endangering state of the patient, a significant dissemination of tumour elements, pathological fractures or a dangerous introduction of major neurovascular formations into the tumour.